PENERAPAN METODE MOBILE-D DALAM PENGEMBANGAN SISTEM PENJUALAN PADA TOKO OPPA FOODS MENGGUNAKAN ANDROID STUDIO - Rohmanu, Ajar; Sulfiati, Putri Aida (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
The proliferation of Internet and technology is spawning business opportunities. One is an android - based app that allows companies or individuals to purchase or sell products online only through smartphones. In this research, design for development of the sales system became an android based in oppa foods' store. The design method for system development is the mobile-d, which consists of the five phases of which is explore phase is tasked with planning and organizing, initialize phase is serves to prepare a list of the needs of the research process, productionize phase is charge to implement all functional needs based on the design already made, stabilize phase is in charge of writing documentation of the building process, test and fix phase is duty to test and to do repairs. The development of the ageing system at oppa foods' store by mobile-d and testing with black box results in a more structured system focused on ordering the product and payment process where the whole menu is functioning for its function.